Contraband tobacco on post-secondary campuses in Ontario, Canada: analysis of discarded cigarette butts - Barkans, Meagan (BioMed Central, 2013)
BACKGROUND: No studies to date have assessed young adults’ use of First Nations/Native tobacco, a common form of contraband tobacco in Canada. This study examined the proportion of First Nations/Native cigarette butts discarded on post-secondary campuses in the province of Ontario, and potential differences between colleges and universities and across geographical regions. METHODS: In 2009, discarded cigarette butts were collected from high-traffic smoking locations at 12 universities and 13 colleges purposively selected to represent a variety of institutions from all 7 health service regions across Ontario. Cigarette butts were identified as First Nations/Native tobacco if they were: known First Nations/Native brands; had names not matching domestic and international legally-manufactured cigarettes; had no visible branding or logos. RESULTS: Of 36,355 butts collected, 14% (95% CI = 9.75–19.04) were First Nations/Native. Use of this tobacco was apparent on all campuses, accounting for as little as 2% to as much as 39% of cigarette consumption at a particular school. Proportions of First Nations/Native butts were not significantly higher on colleges (M = 17%) than universities (M = 12%), but were significantly higher in the North region. CONCLUSIONS: The presence of cheap First Nations/Native (contraband) tobacco on post-secondary campuses suggests the need for regulation and public education strategies aimed to reduce its use. Strategies should account for regional variations, and convey messages that resonate with young adults. Care must be taken to present fair messages about First Nations/Native tobacco, and avoid positioning regulated tobacco as a healthier option than contraband.